Bland embolization of a ruptured hepatoblastoma with massive intraperitoneal hemorrhage - Nariman Nezami, MD; Hans Michell, MD; Christos Georgiades, MD PHD; Elie Portnoy, MD (Radiology Case Reports, 2020)
Purpose: Hepatoblastoma is the most common primary neoplasm of the liver in the pediatric population, usually diagnosed during the first 5 years of life. Patients with large or peripheral hepatoblastomas are at risk for rupture and peritoneal hemorrhage. Image-guided, minimally invasive interventions are offered for controlling hemorrhage. Case presentation: We present a 2-year-old female with an 11.8 cm hepatoblastoma in the right hepatic lobe involving segment 4A, who developed hemodynamic instability on day 8 of induction chemotherapy. Imaging revealed intraperitoneal hemorrhage secondary to her ruptured hepatoblastoma. The patient was successfully treated by celiac artery angiogram and transarterial bland embolization. Conclusion: Transarterial bland embolization of large hepatoblastomas may control and even prevent intraperitoneal/intracapsular hemorrhage, and may also enhance the efficacy of systematic chemotherapy in the pediatric patients with advanced hepatoblastoma.